PERAN TENAGA ADMINISTRASI SEKOLAH DALAM MENINGKATKAN LAYANAN ADMINISTRASI KESISWAAN DI SMP NEGERI 4 PAMMANA KABUPATEN WAJO - Riska; Ardiansyah, Muhammad; Hasan (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study examines the role of school administrative staff in improving student administration services at SMP Negeri 4 Pammana, Wajo Regency, using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The results of the study show that administrative staff play an important role in various student administration services, such as during the new student admission process (creating banners or billboards, brochures, promotions, and assisting in the formation of the admission committee), assisting with new student orientation (providing attendance lists, journals, activity rooms, and monitoring orientation activities), preparing self-development programs (creating activity letters, attendance lists, material requirements, and even serving as presenters), and in reporting student learning progress (acting as report card application administrators and compiling student grade data from teachers). However, the study also found areas that need improvement, particularly in the preparation of student progress reports, which are hindered by inadequate facilities, especially unstable internet connections. Other obstacles include a shortage of administrative staff, limited Wi-Fi access, lack of information technology training, and short working hours, which increase workload and hinder service optimization. Supporting factors for success include the availability of technological facilities (laptops, printers, scanners), sufficient funding, and good collaboration between administrative staff, teachers, and the principal.